Defining and Putting into Practice Tribal Digital Sovereignty - Morris, Traci L. (The journal of community informatics, 2026)
This article advances the concept of Tribal Digital Sovereignty (TDS) as a critical framework for understanding and governing the digital futures of Tribal Nations. TDS encompasses the entire digital ecosystem: infrastructure, software, policy, and human capacity. Drawing on Federal Indian Law, Indigenous governance traditions, and global debates on digital sovereignty, the article situates TDS as both a continuation of longstanding assertions of sovereignty and a necessary response to 21st-century technological challenges.To operationalize this framework, the article adapts Benjamin Bratton’s stack model to highlight how Tribal Nations can exercise sovereignty in digital spaces, for example, by building broadband networks, establishing data governance offices, and developing culturally grounded digital tools. The article concludes by calling for comprehensive strategies that integrate legal infrastructure, capacity building, and economic planning to ensure Tribal Nations are not merely users of global systems but sovereign architects of them. In doing so, it charts a path toward a Sovereign stack aligned with the long-term flourishing of Indigenous Nations in a networked world.